1989
DOI: 10.1148/radiology.173.1.2675183
|View full text |Cite
|
Sign up to set email alerts
|

Bone and soft-tissue lesions: diagnosis with combined H-1 MR imaging and P-31 MR spectroscopy.

Abstract: The feasibility of combined magnetic resonance (MR) imaging and surface coil phosphorus-31 MR spectroscopy at 1.5 T was examined in a clinical study of 34 patients before biopsy of bone or soft-tissue lesions of the extremity and trunk. The results confirmed the inability of MR imaging alone to distinguish most benign lesions from malignant ones. Malignant lesions were distinguished from benign lesions on the basis of significantly higher mean peak ratios of phosphomonoester (PME) to beta-nucleoside triphospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…Also tumours demonstrate a wide range of pH within them. Thus, pH may not be useful in determining the types of tumours [6,24]. Our study showed pH of all pathologies tending towards the acidic range, the values were not statistically significant to differentiate the grade or types of tumours and non-neoplastic lesions.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…Also tumours demonstrate a wide range of pH within them. Thus, pH may not be useful in determining the types of tumours [6,24]. Our study showed pH of all pathologies tending towards the acidic range, the values were not statistically significant to differentiate the grade or types of tumours and non-neoplastic lesions.…”
contrasting
confidence: 57%
“…P MRS is an established technique for evaluating tumours of extremity, head, neck and liver [5][6][7][8][9]. It allows non invasive characterization of phosphate containing compounds within tumour cells and determination of energy status and pH [9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of NMR spectroscopy to detect metabolite profiles indicative of tumor differentiation is important because in many tumor types, particularly liposarcoma, the histologic type is one of the most important factors in predicting risk for relapse and overall survival. To date, studies of human soft-tissue sarcomas have largely been confined to 31p_ NMR in vivo studies (15)(16)(17)(18)(19)(20). a3C-NMR spectroscopy offers more detailed biochemical information relating to lipid content and composition than does 31P-NMR.…”
mentioning
confidence: 99%
“…With this new system it was possible to sample multiple values of the tissue partial oxygen pressure (PO,). Also 31P-MRS was tested in human neoplasms (10,11) using magnets with a field strength of typically 1.5 T. The attraction was that phosphorus spectroscopy was non-invasive, not painful and could be performed repeatedly, which gave a unique opportunity to monitor the responsiveness to a specific treatment. Moreover, it was documented to provide specific information about the in vivo metabolic status of mouse tumour models using high field scanners of about 4.7 T (12).…”
mentioning
confidence: 99%